Sanitation, Drainage, and Plumbing System Utilities in Gedung Kuliah Bersama 2 (GKB 2) Universitas Muhammadiyah Semarang - Isnaini Aulia Dewi, Clarisa; Dwi Indarti, Fitri; Kinasih, Kania; Eko Santoso, Rohman (Architecture Study Program, Faculty of Engineering and Computer Science, Universitas Muhammadiyah Semarang, 2024)
In constructing high-rise buildings such as Gedung Kuliah Bersama 2 Universitas Muhammadiyah Semarang, the right planning and design stages are very important requirements in the process. The utility system of a building is a series of complementary things that must be planned from the beginning before the building operates. Utility systems are part of a building's success in meeting or accommodating the needs of its users. Utilities learn a lot about the effectiveness of space division in-room programming, access, property details, and other things that support the function of a building. This research is based on a field survey that focuses on the type of sanitation, drainage, and piping system (SDP) in building utilities. This study aims to analyze the performance of buildings in high-rise buildings in the education sector, namely the Gedung Kuliah Bersama 2. The utility system in the Gedung Kuliah Bersama 2 has met SNI (Indonesian National Standard) standards with a fully used connected system along with the distribution of power and capacity in the area within the building which is supported by modern and sophisticated equipment to be more effective and efficient in supporting building performance.